ROLE OF COMMUNICATION TOOLS IN THE PROMOTION OF MUSIC: संगीत के प्रचार प्रसार में संचार साधनों की भूमिका - Yadav, Gaurav (International Journal of Research -GRANTHAALAYAH, 2015)
The first half of the twentieth century can be termed as the heyday of the scientific revolution, where some of the instruments were invented under the scientific inventions that accelerated the propagation of music. A scientific invention in the field of music in the early stages of communication means special importance, which revolutionized the world not only in the field of Indian music but it was the advent of radio. It was established in India in 1926 AD. In 1937, the name of the Indian State Broadcasting Service was changed to All India Radio. बीसवीं शताब्दी के पूर्वार्द्ध को वैज्ञानिक क्रांति के अभ्युदय का समय कहा जा सकता है, जहाँ वैज्ञानिक अविष्कारों के अंतर्गत कुछ ऐसे उपकरणों का अविष्कार हुआ जिन्होंने संगीत के प्रचार-प्रसार को तीव्रता प्रदान की। संचार साधनों के प्रारंभिक दौर में संगीत के क्षेत्र में एक वैज्ञानिक अविष्कार का विशेष महत्व है ,जिसने भारतीय संगीत के क्षेत्र में ही नहीं वरन् विश्व में क्रांति ला दी यह था रेडियो का आगमन। भारत में इसकी स्थापना सन् १९२७ ई. में हुई। सन् १९३६ ई. में इंडियन स्टेट ब्रॉडकास्टिंग सेवा का नाम बदलकर आकाशवाणी कर दिया गया।